1999
DOI: 10.1515/cclm.1999.076
|View full text |Cite
|
Sign up to set email alerts
|

Automated Prozone Effect Detection in Ferritin Homogeneous Immunoassays Using Neural Network Classifiers

Abstract: The application of turbidimetric homogeneous immunoassays made the determination of several plasma components widely available. The sensitivity and accuracy of these assays are appropriate enough for routine laboratory use; however, in the case of many pathologically high concentration samples, prozone effect (high dose hook effect) can be observed, that leads to false-negative determination. Up to the present there are no cost-effective algorithms available for the safe detection of the prozone effect. Pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Our approach avoids this by having upfront dilutions programmed on the instrument. In addition, our approach is simple and does not require the expertise to implement more complex approaches, such as neural learning networks ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach avoids this by having upfront dilutions programmed on the instrument. In addition, our approach is simple and does not require the expertise to implement more complex approaches, such as neural learning networks ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some have instituted a separate orderable for when there is clinical suspicion hook effect might occur ( 5 ). Others have employed neural learning networks to evaluate reaction curves and detect hook effect ( 6 ). With regards to lateral flow assays, recent efforts have been reported that investigate reaction kinetics to reduce hook effect ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many results have shown that ANNs are suitable tools for medical classification and prediction tasks and examples of these applications can be seen in Refs. (9)(10)(11)(12)(13)(14)(15)(16). The ability of ANNs to differentiate benign from malignant breast cancer has been tested, and correct diagnoses prediction of 80% of the tested patients has been observed (10).…”
Section: Introductionmentioning
confidence: 99%
“…Also predictions of antibiotic concentrations in blood plasma (11), drug release control (12) and glucose control models to improve diabetic care (13) using ANNs have shown satisfactory results. Therefore, the application of this methodology in clinical analysis may optimize the diagnostic utility of laboratory data (10,14,17), reduce the number of unnecessary biopsies (18), and develop specific software applications (9,15,16,19). Moreover, the increasing use of computational methodologies in clinical laboratories has shown a significant and profound effect on how they are organized, staffed, equipped, and operated (20).…”
Section: Introductionmentioning
confidence: 99%